Senam sebagai Upaya Pencegahan Insomnia pada Lansia - Najihah; Pailungan, Ferly Yacoline; Iskandar, Ayuk Cucuk; Wijayanti, Dewi; Ose, Maria Imaculata (Window of Community Dedication Journal, 2023)
Sleep disturbance is something that is very disturbing for health. Sleep disorders are most common in the elderly, this happens because there are many physiological changes in the elderly that can make the elderly more vulnerable to several diseases. These changes will occur continuously as we age. In overcoming insomnia, exercising regularly is one of the efforts that can be done. One of the exercises that can be done is Elderly Gymnastics. One review explained that elderly gymnastics has several benefits, including psychological benefits, namely improving sleep quality and reducing insomnia levels. The method used in this activity is a demonstration of the implementation of elderly gymnastics as an effort to prevent insomnia whose target is a group of elderly people at the Almarhama Social Home in Tarakan City. The results of this activity show the enthusiasm of the elderly to do elderly gymnastic activities to improve their sleep quality. So, it is hoped that the social institution will carry out elderly gymnastic activities regularly once a week. The output of this activity is the publication of articles on the results of activities in indexed / reputable national journals, and become study material in related courses.